Culinary Hygiene and Sanitation: A Systematic Literature Review - Zaitun (Jurnal Penelitian Pendidikan IPA, 2024)
Healthy food refers to food that is both sanitary and nourishing. Edible sustenance Hygienic food refers to food that is free from pathogens and contaminants that can pose a health risk. Food processed products typically exhibit vulnerabilities in terms of their safety, including biological or microbiological, chemical, and physical dangers. The occurrence of hazards or pollution, typically resulting from substandard raw materials, processing techniques, and insufficient sanitation and hygiene practices, has raised concerns regarding the awareness of workers or producers involved in handling processed food. This research aims to investigate the topic of Culinary Hygiene and Sanitation through a systematic review of existing literature. This review was conducted utilizing the latest and most advanced methodologies, following the recommended reporting items for reviews and meta-analyses (PRISMA) standards. The findings of this study clarify that food plays a multifaceted role and serves various purposes, including promoting health, reflecting political and social status, exerting power and fostering cooperation, influencing social and economic standing, embodying cultural values, responding to population density, reflecting changing times, and adhering to principles of hygiene and sanitation. The key elements of the facility are the physical location and structure, the sanitary facilities, the kitchen area, the dining room, and food storage area, the handling of food ingredients and prepared food, the food processing area, the storage area for food ingredients and prepared food, the food serving area, the presentation of food, the equipment used, and the labor involved.